Ejection Fraction Decline and Cardiotoxicity Following Anthracycline Chemotherapy: A Risk-Focused Study from an Indonesian Tertiary Care Center - Rizkyastari Onny; Tutik Harjianti; Pendrik Tandean; Syakib Bakri; Himawan Sanusi; Andi Alfian Zainuddin (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Anthracycline chemotherapy is a cornerstone of cancer treatment but poses a risk of cardiotoxicity, often presenting as cancer therapy–related cardiac dysfunction (CTRCD). Monitoring left ventricular ejection fraction (LVEF) is essential to detect early cardiac impairment and support safer treatment strategies.Aim. To assess LVEF changes after six cycles of anthracycline therapy and identify predictive factors associated with CTRCD.Materials and methods. This observational pre–post study included 74 patients treated with anthracyclines at Dr. Wahidin Sudirohusodo Hospital, Makassar, from 2024 to 2025. LVEF was measured via echocardiographic surveillance before and after treatment. Cardiotoxicity was defined as a ≥10 % decrease in LVEF to ≤50 %. Statistical tools included Wilcoxon signed-rank test, Chi-square, ROC curve analysis, and logistic regression.Results. The mean LVEF significantly declined from 63.08 % to 56.76 % (p = 0.001). CTRCD occurred in 20.3 % of patients. Risk factors independently associated with cardiotoxicity included age ≥51 years (OR 2.80; p = 0.016) and cumulative anthracycline dose ≥457.5 mg/m² (OR 3.25; p = 0.004). When both factors were present, the risk increased nearly sixfold (OR 5.75; p = 0.001).Conclusions. CTRCD was observed in one-fifth of patients following anthracycline therapy, with age and dose being significant contributors. These findings support the integration of risk-based echocardiographic surveillance into oncology care to ensure early detection and mitigate long-term cardiac complications.